1993
DOI: 10.1063/1.858634
|View full text |Cite
|
Sign up to set email alerts
|

The configurations of a FENE bead-spring chain in transient rheological flows and in a turbulent flow

Abstract: The changes in the configuration of a FENE bead-spring chain in a direct numerical simulation of turbulent channel flow and in some simple rheological flows are examined. Unraveling occurs both in uniaxial and shear flows, but the uniaxial flow is more effective. A vortex with a large rotation rate perpendicular to the principal strain of a uniaxial flow has only a minor retarding effect while a small rotation rate delays the unraveling substantially. In a turbulent flow, the chain unravels the most in the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…By comparing the performance of the various polymer models in the same flow field, we obtain a quantitative estimate of the error associated with the FENE-P model. Our approach is similar to the one taken by Zhou and Akhavan (2003) and others (Massah and Hanratty 1997, Massah et al 1993. However, those studies focused on inhomogeneous turbulent channel flow, where the statistics of the trajectory are a strong function of the initial condition.…”
Section: Introductionmentioning
confidence: 72%
“…By comparing the performance of the various polymer models in the same flow field, we obtain a quantitative estimate of the error associated with the FENE-P model. Our approach is similar to the one taken by Zhou and Akhavan (2003) and others (Massah and Hanratty 1997, Massah et al 1993. However, those studies focused on inhomogeneous turbulent channel flow, where the statistics of the trajectory are a strong function of the initial condition.…”
Section: Introductionmentioning
confidence: 72%
“…Massah and co-workers performed simulations of a FENE beadspring chain in a direct numerical simulation of turbulent channel flow and found that in the buffer region the extension and orientation of the polymer fluctuate with time, and the transient polymer stretch is significantly larger than its coiled equilibrium length. 35 This result is only seen when the product of the polymer relaxation time and the characteristic wall shear rate ͑a nominal Weissenberg number We͒ exceeds a certain threshold. Later work by the same group found that the stresses introduced by the stretched polymers in a turbulent flow lead to added dissipations, both positive and negative.…”
Section: Polymers In Lagrangian Time-dependent Flowsmentioning
confidence: 99%
“…The model consisting of only N = 2 beads is known as the finitely extensible nonlinear elastic (FENE) dumbbell model [1]. The molecular approach is suitable for studying the deformation of passively transported polymers [9][10][11][12][13][14][15][16][17][18][19][20][21]. Molecular dynamics has also been employed in combination with standard Eulerian techniques to simulate viscoelastic flows (see the CONNFFESSIT [22,23] and BCF [24] approaches).…”
Section: Introductionmentioning
confidence: 99%